Photochemical Synthesis of Sericin-Coated Gold Nanorods and Their Antibacterial Activity under Low-Level Near-Infrared Light - Poomrattanangoon, Sasiprapa (Langmuir : the ACS journal of surfaces and colloids, 2024)
Gold nanorods (GNRs) are unique nanoparticles with easily functionalized surfaces, multiple synthesis methods, photothermal conversion, and surface plasmon resonance effects. These properties make GNRs suitable for various biological applications. However, a rapid synthesis of GNRs using less toxic chemicals is needed. The photochemical method is a viable option that can synthesize GNRs quickly while using fewer chemicals. A photochemical method is reported for the synthesis of GNRs using Irgacure-2959 as a reducing agent. This method could be used to synthesize GNRs with a rod-like shape within 30 min. Additionally, GNRs were coated with sericin (GNRs-SC) to further reduce their toxicity in human dermal fibroblast adult cells. Low-level near-infrared (NIR) light was applied to enhance the photothermal therapy of both GNRs and GNRs-SC. The results showed that GNRs and GNRs-SC under low-level NIR light have enhanced antibacterial activity against Staphylococcus aureus and Escherichia coli, as well as antibiofilm activity against S. aureus. Furthermore, GNRs-SC showed good biocompatibility with antibacterial and antibiofilm activities. These results indicate that GNRs-SC are good candidates for various biological applications